GAMBARAN KINERJA KADER POSYANDU DENGAN KEPUASAN IBU BALITA DI POSYANDU DESA WAKASIHU KABUPATEN MALUKU TENGAH - Moh. Dahlan Sely (Pusat Riset dan Inovasi Nasional, 2021)
Cadres are voluntary workers recruited from, by and for the community who are tasked with assisting the smooth running of health services. The performance of Posyadu cadres experienced a decline in the early 2000s as a result of a prolonged multi-dimensional crisis, this is known because there were reports of malnutrition from various parts of the country. The decline was felt following the lack of cadre skills, no Posyandu operational support, inadequate facilities and infrastructure and weak coaching. The purpose of this study was to describe the performance of posyandu cadres with the satisfaction of mothers of children under five at the Posyandu, Wakasihu Village, Central Maluku Regency. The type of research used is descriptive research. The population in this study were all mothers under five who visited the posyandu as many as 30 toddlers. The sampling technique in this study is total sampling, which means that all populations are sampled. So that the sample found in this study amounted to 30 people or respondents. The results showed that the mothers under five studied who said that the performance of cadres was good amounted to 13 people (56.7%), and the performance of cadres was not good amounted to 17 people (43.3%). Furthermore, from the 30 respondents who were examined, it can be seen that the number of respondents who said they were satisfied with the performance of the cadres were 18 people (60.0%), and respondents who said they were not satisfied were 12 people (40.0%). It was concluded statistically and illustrated that the performance of cadres still had opinions from mothers of children under five that they were not good at providing services at the posyandu. It was also concluded that statistically some respondents or mothers of toddlers still said that they were satisfied with the performance of cadres.